CORRELATION OF PREDISPOSING, ENABLING, AND NEED FACTOR OF PROGRAM KELUARGA HARAPAN PARTICIPANTS TOWARD UTILIZING PRIMARY HEALTHCARE - Sendhi Tristanti Puspitasari; Roesdiyanto; Dita Maulidya Rizka (Universitas Airlangga, 2023)
Introduction: Program Keluarga Harapan (PKH) is a program aimed to reduce the vulnerability of the poor through conditional cash assistance for household need such as access to health and education services, immunization, and family nutrition fulfillment. PKH participants are given health insurance (KIS) facility, especially in Penerima Bantuan Iuran (PBI), to access health services. Total PBI participants in 2019 reached 28.81% with healthcare utilization only 13.34%. Preliminary studies showed that not all PKH participants have KIS and use health services. The aim of the study is to find out the correlation of predisposing, enabling, and need factors of PKH participants in the Thematic Village toward utilizing health services in Kendalkerep Primary Healthcare. Methods: This study is an analytic-observational study and cross-sectional approach with subjects all of PKH participants in Kampoeng Lampion Wangi, Kampung Warna Warni Jodipan, and Kampung Tridi. Data are analyzed by logistic regression and correlational test. Result: Results of analysis show that there is significant correlations of predisposing factor such as education (β = 1.689), employment status (β = 1.466); enabling factor such as health insurance (β = 3.045), access to healthcare (β = 2.819); and need is a perception of illness (β = 2.767) toward Kendalkerep Primary Healthcare by PKH Thematic Village participants. Conclusion: Based on Nagelkerke determination coefficient, health insurance and access is a dominant factor which affects the utilization Kendalkerep Primary Healthcare of 46% with correlational strength fair and correlational direction positive.